A Deterministic Model for Remanufacturing Inventory for Reverse Supply Chain - Mohapatra, Sasmita; N.Mahapatra, R.; B.Biswal, B.; Balabantray, Bunil; K.behera, A. (International Journal of Engineering and Technology, 2018)
Reverse logistics is a pervasive business activity. Companies spend a lot of time and money in fine tuning their forward supply chain while ignoring the reverse supply chain. Conventional supply chain processes, driven by customer demand which carry goods from suppliers through manufacturers and distributors to the final customers. Physical goods donâ€™t simply vanish once they have reached the customer.Â In todayâ€™s trend reuse of products and materials (repair, remanufacturing, refurbishing and recycling) and recovering value incorporated in them is a common phenomenon. The paper deals with controlling inventory for a remanufacturing system in which the stationary demand is fulfilled by remanufactured products as well as newly purchased products. The model is based on the assumption that customer return items are remanufactured at a fixed rate. Remanufactured items can be treated as the new products. The economic order quantity for the manufactured and remanufactured items is calculated simultaneously.Â Â